An Analysis of the Structure and Thermal Conductivity of Hollow Microsphere Filled Syntactic Foams - Petkova-Slipets Rositsa; Zlateva Penka (Civil and Environmental Engineering, 2019)
The influence of types and parameters of hollow microspheres in the composition of syntactic foams on their structure and coefficient of thermal conductivity has been studied. By using structural and thermal analysis it has been found that the volume concentration and the size of the ceramic and glass hollow microspheres have a strong impact on the density and thermophysical properties of the thin syntactic foams coatings. It has been shown that the best heat insulating properties belong to syntactic foam with composition of 60 vol. % ceramic microspheres with particle size of 1 - 40 μm (k = 0.029 W/m·K, R = 0.008 (m2·K)/W) and with composition of 80 vol. % glass hollow microspheres with particle size of 9 - 25 μm (k = 0.087 W/m·K, R = 0.008 (m2·K)/W). The results demonstrate that application of syntactic foams as thin insulating coatings is appropriate and they are an energy efficient material with number of benefits compare with the common thermal insulators.